2022
DOI: 10.3390/s22239519
|View full text |Cite
|
Sign up to set email alerts
|

Study on a Flexible Odor-Releasing Device for Olfactory Training

Abstract: Olfactory training has been shown to be effective in treating olfactory dysfunction. However, there are hardly any devices that can regularly and quantificationally release odors for olfactory training. A new odor-releasing device, which is low-cost, customizable, semi-automatic, and flexible, was developed in this study. The operation of the device can be easily achieved by the examiner, or even by the participant, simply by pressing a few buttons. A controller system with 15 individual relays was employed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Covington et al [17] reported the development of a simple yet innovative multichannel olfactory display, which can release up to eight different liquid phase aromas (essential oils) using a thermal mechanism. Peng et al [18] developed a new odor-releasing device, which is low-cost, customizable, semi-automatic, and flexible. The specific requirements of different participants can be used to customize the odorants and their concentrations stored in the scent bottles.…”
Section: Introductionmentioning
confidence: 99%
“…Covington et al [17] reported the development of a simple yet innovative multichannel olfactory display, which can release up to eight different liquid phase aromas (essential oils) using a thermal mechanism. Peng et al [18] developed a new odor-releasing device, which is low-cost, customizable, semi-automatic, and flexible. The specific requirements of different participants can be used to customize the odorants and their concentrations stored in the scent bottles.…”
Section: Introductionmentioning
confidence: 99%